Purification and functional characterisation of rhinocerase, a novel serine protease from the venom of Bitis gabonica rhinoceros. - Sakthivel Vaiyapuri; Robert A Harrison; Andrew B Bicknell; Jonathan M Gibbins; Gail Hutchinson (PLoS ONE)
Background Serine proteases are a major component of viper venoms and are thought to disrupt several distinct elements of the blood coagulation system of envenomed victims. A detailed understanding of the functions of these enzymes is important both for acquiring a fuller understanding of the pathology of envenoming and because these venom proteins have shown potential in treating blood coagulation disorders. Methodology/principal findings In this study a novel, highly abundant serine protease, which we have named rhinocerase, has been isolated and characterised from the venom of Bitis gabonica rhinoceros using liquid phase isoelectric focusing and gel filtration. Like many viper venom serine proteases, this enzyme is glycosylated; the estimated molecular mass of the native enzyme is approximately 36 kDa, which reduces to 31 kDa after deglycosylation. The partial amino acid sequence shows similarity to other viper venom serine proteases, but is clearly distinct from the sequence of the only other sequenced serine protease from Bitis gabonica. Other viper venom serine proteases have been shown to exert distinct biological effects, and our preliminary functional characterization of rhinocerase suggest it to be multifunctional. It is capable of degrading alpha and beta chains of fibrinogen, dissolving plasma clots and of hydrolysing a kallikrein substrate. Conclusions/significance A novel multifunctional viper venom serine protease has been isolated and characterised. The activities of the enzyme are consistent with the known in vivo effects of Bitis gabonica envenoming, including bleeding disorders, clotting disorders and hypotension. This study will form the basis for future research to understand the mechanisms of serine protease action, and examine the potential for rhinocerase to be used clinically to reduce the risk of human haemostatic disorders such as heart attacks and strokes.